Utilization of insecticide treated nets among pregnant women in sodo zuria woreda Southern Ethiopia - Nadew, Jemaneh; Obsa, Mohammed Suleiman; Alemayehu, Akalewold; Haji, Yusuf (Frontiers in Tropical Diseases, 2022)
Background: The malaria control strategy has shown an improvement in providing services and allocating resources to enhance malaria elimination. The world malaria report indicated that there was a marked increment of insecticide treated net (ITNs) utilization among pregnant women. However, in Ethiopia, the number of households with possession and utilization of ITNs is still far behind the WHO recommendations. Hence, this study was aimed to measure the magnitude of ITN utilization and to identify factors associated with its utilization among pregnant women from April 4, 2021 to April 15, 2021 in Sodo Zuria Woreda, in Wolaita Zone, Southern Ethiopia. Methods: A community based cross-sectional study was employed. Data were collected using interviewer administered pretested, structured questionnaires. Simple random sampling method was used to select 459 pregnant women. Data were entered into Epi Info version 7 and then exported to statistical package for the social sciences for further analysis. We used time period for data collection of current study. Binary’s logistic regression was used to determine factors affecting insecticides treated net (ITN) utilization. Adjusted Odd Ratios (OR) with 95% CI was used to measures the strengths of associations. Results: Of 435 surveyed households with pregnant women, 341(78.39%) with 95% Confidence Interval (CI) (74.5%, 82.3%) possessed at least one insecticide treated net. Among them, 194(56.89%) with 95% CI (51.6%, 61.7%) interviewees had self-reported as they slept under insecticide treated net on the night preceding the data collection day. Utilization of insecticide treated nets by other family members, AOR: 6.615(95% CI: 3.358, 13.032), knowledge that the use of insecticide treated nets can prevent malaria, AOR: 3.221(95% CI: 1.737, 5.974), Sleeping under insecticide treated nets, AOR: 3.726(95% CI: 1.974, 7.034), and Attending ANC follow up visits, AOR: 1.956(95% CI: 1.097), were found to be significantly associated factors with pregnant women’s insecticide treated net utilization. Conclusion: The number of households with pregnant women who had possession and utilization of ITNs was much lower than the recommendations set by WHO. Therefore, information dissemination to malaria high risk groups about insecticide treated net utilization and replacement of worn-out insecticide treated nets should be emphasized.